Effects of low-load resistance training with blood flow restriction on muscle fiber myofibrillar and extracellular area - Libardi, Cleiton A.; Godwin, Joshua S.; Reece, Tanner M.; Ugrinowitsch, Carlos; Herda, Trent J.; Roberts, Michael D. (Frontiers in Physiology, 2024)
Blood flow restriction applied during low-load resistance training (LL-BFR) induces a similar increase in the cross-sectional area of muscle fibers (fCSA) compared to traditional high-load resistance training (HL-RT). However, it is unclear whether LL-BFR leads to differential changes in myofibrillar spacing in muscle fibers and/or extracellular area compared to HL-RT. Therefore, this study aimed to investigate whether the hypertrophy of type I and II fibers induced by LL-BFR or HL-RT is accompanied by differential changes in myofibrillar and non-myofibrillar areas. In addition, we examined if extracellular spacing was differentially affected between these two training protocols.Twenty recreationally active participants were assigned to LL-BFR or HL-RT groups and underwent a six-week training program. Muscle biopsies were taken before and after the training period. The fCSA of type I and II fibers, the area occupied by myofibrillar and non-myofibrillar components, and extracellular spacing were analyzed using immunohistochemistry techniques. Despite the significant increase in type II and mean (type I + II) fCSA (P < 0.05), there were no significant changes in the proportionality of the myofibrillar and non-myofibrillar areas (~86% and ~14%, respectively (P > 0.05)), indicating that initial adaptations to LL-BFR are primarily characterized by conventional hypertrophy rather than disproportionate non-myofibrillar expansion. Additionally, extracellular spacing was not significantly altered between protocols. In summary, our study reveals that LL-BFR, like HL-RT, induces skeletal muscle hypertrophy with proportional changes in the areas occupied by myofibrillar, non-myofibrillar, and extracellular components.